Furosemide and Ductus Arteriosus Closure in Very-Low-Birth-Weight Preterm Infants: A Comprehensive Retrospective Study - Chi-Mei Kuo; Pin-Chun Su; Shu-Ting Yang; Hao-Wei Chung; Hsiu-Lin Chen (MDPI AG, 2024)
Ductus arteriosus closure may be delayed in preterm infants, and prostaglandin, a vasodilator, can affect ductal patency. Furosemide can increase renal prostaglandin synthesis, so its net effect on patent ductus arteriosus (PDA) is uncertain. Our goal is to explore the relationship between furosemide and spontaneous ductal closure in very-low-birth-weight preterm infants. Our treatment for PDA involves fluid restriction initially and furosemide administration for hemodynamically significant PDA until closure is confirmed by the echocardiogram. We enrolled 105 infants from 1 January 2019 to 30 June 2022 and evaluated the impact of furosemide on ductal closure, including exposure duration and cumulative dose. There is no correlation between furosemide exposure and spontaneous ductal closure (p = 0.384). Furosemide exposure does not delay the postmenstrual age at which spontaneous ductal closure occurs (p = 0.558). The time for spontaneous ductal closure is positively associated with furosemide prescription days (coefficient value = 0.547, p = 0.026) and negatively with gestational age (coefficient value = −0.384, p = 0.062). The prescription of furosemide does not impact the probability or time duration of ductus arteriosus spontaneous closure. The cumulative dose of furosemide has minimal impact on ductal closure. The correlation between furosemide exposure duration and ductal patency duration is likely due to our treatment protocol, with gestational age being a significant factor.